A study of teacher practices in supporting the information processing of children with intellectual disabilities - Özbaşi, Durmuş; Kalkan, Sinan; Arcagok, Serdar; Erbaş, Yahya Han; Erdamar, F. Selim; Mertol, Huseyin (Duzce University, Faculty of Education, 2025)
Information processing in children with intellectual disabilities is crucial for understanding their cognitive development, recognizing their deficits in learning information and individualizing educational programs. The aim of this study was to explore the implementation experiences of special education teachers and elementary school teachers working with children with intellectual disabilities in relation to information processing, and to determine what kind of adaptations/regulations they have made to support information processing for these children. To this end, a generic design, one of the qualitative research designs, was used in the study. The study group comprised 61 teachers, including 32 special education teachers and 29 elementary school teachers. The data were collected using an interview technique and content analysis was used to analyze the data. The findings show that teachers working in both educational settings (special education teachers and elementary school teachers) have inadequate knowledge of information processing, and moreover, teachers in both groups do not make accommodations for information processing activities that are extremely important for children with intellectual disabilities. Therefore, teachers need to make pedagogical, physical and equipment-related accommodations to help improve the information processing work of children with intellectual disabilities. © 2025, Duzce University, Faculty of Education. All rights reserved.
Keywords: Information processing model; Instructional adaptation; Intellectual disability; Learning